Redox processes at iron hydroxide layers formed on platinum substrates in alkaline solutions - Galindo, M. C. (1990)
Redox processes taking place at precipitated hydrous iron hydroxide layers chemically formed on platinum substrates in sodium hydroxide solutions are investigated at 25°C. The electrochemical behaviour of these layers depends considerably on the electroreduction level reached in chargedischarge cycles. The accumulation of Fe3O4 during oxidation-reduction cycles can produce an increasing irreversibility of the Fe(II)/Fe(III) redox couple. Data are compared to results obtained with iron hydroxide layers formed by electrochemical and chemical methods on massive iron electrodes. Results are discussed in terms of a composite structure for the iron hydroxide layers.